The first historical and legal research in Kazakhstan: posing problems of customary law (Journal of actual problems of jurisprudence, 2019)
In Kazakhstan, the origins of the formation and development of legal science originate from historical and legal research: the history of the state and law. This article is devoted to an attempt to analyze the formation of historical and legal research in Kazakhstan, which has its own characteristics. The formation of the subject and object of historical and legal research is due to the influence of the Russian, Soviet Russian tradition of scientific research.